Studies on fracture behaviour of lightly reinforced concrete beams using digital image correlation - Rao, G. Appa; Nagesh, H.E. (Journal of Structural Engineering, 2024)
Lightly reinforced concrete (RC) beams are fracture sensitive, which can be analysed with accuracy using fracture mechanics principles. This paper describes fracture behaviour of lightly reinforced concrete beams using digital image correlation (DIC) and also discusses short comings related to prediction of minimum tension reinforcement, as per IS 456-2000, in beams made of high strength concrete. The images acquired using two dimensional (2D)-DIC technique are correlated with undeformed image for capturing full field displacements, horizontal strain, crack width and crack length. The crack mouth opening displacement (CMOD) and mid-span deflection recorded using DIC have been compared with those measured from linear variable differential transducer (LVDT), are found to be in good agreement. Overall, DIC technique has been observed to be effective for predicting the fracture parameters of lightly RC beams. An experimental study has been carried out to understand the influence of beam size and compressive strength of concrete on behaviour of lightly RC beams. It has been found that tensile cracking stress in concrete decreases with increase in beam depth. The minimum tension reinforcement as per IS 456-2000 cannot ensure stable behaviour and hence unsafe for high strength concrete beams. Thus, the provision for minimum reinforcement needs modification incorporating compressive strength of concrete and beam size.